INCREASING THE COMPETITIVENESS OF WET CAKE SMEs THROUGH PRODUCT DIVERSIFICATION AND PACKAGING RE-BRANDING IN PANDANSARI VILLAGE - Hari Muharam; Ramlan Ramlan; May Mulyaningsih (International Journal of Engagement and Empowerment (IJE2), 2026)
The micro-scale culinary sector in Pandansari Village, Bogor Regency, has promising economic potential. However, nine small and medium-sized cake-making small and medium-sized enterprises (SMEs) in this region are experiencing stagnation due to a lack of product innovation, both in terms of flavor variants, shapes, and conventional packaging. This condition reduces product competitiveness and hinders penetration into modern markets and the digital marketing ecosystem. This Community Service (PKM) activity aims to increase the capacity of SME partners in diversifying products andre-brandingpackaging to increase added value (perceived value) and product competitiveness. The approach used isParticipatory Action Research (PAR) which includes the observation stage, education (product management training), production assistance (prototyping), and evaluation. This activity resulted in a significant increase in partners' understanding of the strategy.line fillingand packaging. Practically, 100% of partners succeeded in creating innovative new flavor variants (matcha, premium cheese, red velvet) and modify the shape of the cake intobite-size. In addition, partners have successfully implemented packagingfood gradevariouswindow boxcomplete with informative labeling as brand identity (brandingProduct diversification and packaging standardization interventions have proven effective in transforming SME products into high-value products that meet aesthetic and hygiene standards to compete in modern retail and marketing markets.online.